Scalable Cloud Application Deployment Service for Versatile Cloud Service Deployment and Configuration - Habala, Ondrej; Šeleng, Martin; Habala, Michal; Stuhl, Ľubor; Staňo, Michal; Hluchý, Ladislav (Computing and Informatics, 2024)
<span data-slate-fragment="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">We present a cloud management service called RAIN. It has been designed specifically for versatility and scalability of operation, allowing for the processing of a large number of requests at the same time. Its operation is transactional and controlled by a workflow of operations forming one requisition. Requisitions and their operations can be executed in parallel, allowing for high throughput and scalability of the controlled cloud environment(s). The service is being used in day-to-day operations in a commercial environment. It is also designed for high failure tolerance, which is necessary when operating on third party cloud infrastructures. It has been developed and actively used for several years now, giving us a mature tool with many important features added over time, allowing for practical day-to-day operations. The architecture of the service is open and easily extendable to allow the inclusion of new cloud services of various types – PaaS providers as well as providers of higher-level services. The service is accessed via an asynchronous REST API. It allows the caller to resume execution and not wait for cloud deployment operations to take an arbitrary amount of time to finish, receiving progress updates via a simple callback REST API.